2020
DOI: 10.3174/ajnr.a6689
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of In-Stent Restenosis for Symptomatic Intracranial Atherosclerotic Stenosis: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: In-stent restenosis affects long-term outcome in patients with intracranial atherosclerotic stenosis. PURPOSE:The aim of this meta-analysis was to evaluate the incidence and risk factors of in-stent restenosis.DATA SOURCES: All literature that reported in-stent restenosis was searched on PubMed, Ovid EMBASE and Ovid MEDLINE data bases.STUDY SELECTION: Original articles about stents for symptomatic intracranial atherosclerotic stenosis were selected.DATA ANALYSIS: Meta-analysis was conducted to deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 62 publications
3
38
0
Order By: Relevance
“…A previous study [ 22 ] demonstrated that as the Lp-PLA2 level increases, the risk of coronary heart disease and stroke increases, especially in the elderly and asymptomatic people with atherosclerotic disease. A meta-analysis [ 23 ] has shown that Lp-PLA2 level is linearly and logarithmically related to coronary heart disease and vascular death. A cohort study [ 24 ] has suggested that Lp-PLA2 measured in the acute phase is associated with 1-year mortality, indicating that Lp-PLA2 may not be affected by acute inflammatory events, but is a specific indicator for vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 22 ] demonstrated that as the Lp-PLA2 level increases, the risk of coronary heart disease and stroke increases, especially in the elderly and asymptomatic people with atherosclerotic disease. A meta-analysis [ 23 ] has shown that Lp-PLA2 level is linearly and logarithmically related to coronary heart disease and vascular death. A cohort study [ 24 ] has suggested that Lp-PLA2 measured in the acute phase is associated with 1-year mortality, indicating that Lp-PLA2 may not be affected by acute inflammatory events, but is a specific indicator for vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of ISR in our analysis was similar with a systematic review and meta-analysis by Peng et al, which had a 14.8% ISR rate. 7 The SAMMPRIS Trial, a prospective randomized controlled…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial angioplasty and stenting are beneficial for selected patient cohorts and have been used widely in many experienced centers (9,31). After stent placement, imaging surveillance is necessary to monitor for in-stent restenosis (12). Computed tomography angiography is limited for poststenting evaluation due to metal beam hardening artifact obscuring luminal evaluation (14).…”
Section: Discussionmentioning
confidence: 99%
“…An accurate evaluation of stenosis is needed for appropriate patient selection for angioplasty and stenting (10,11). Post-stenting arterial segment evaluation is also important considering the re-stenosis rate after stenting is 11.9-17.9% (12). This evaluation, however, is challenging for CTA, CE-MRA, and 3D-TOF-MRA due to beam hardening artifacts or magnetic susceptibility artifacts (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%